Primary Health Care during the COVID-19 pandemic in Fortaleza, Brazil: associated factors and pattern of use by mothers and children up to 18 months of age - Luciano Lima Correia; Márcia Maria Tavares Machado; David Augusto Batista Sá Araújo; Yuri Valentim Carneiro Gomes; Maria Suelly Nogueira Pinheiro; Hermano Alexandre Lima Rocha; Denise Lima Nogueira; Geziel dos Santos de Sousa; Simone Farias-Antuñez; Márcia Caldas Castro (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: To analyze the delay or failure to seek primary health care by the mother-child dyads during the COVID-19 pandemic, a practice that has a high potential to increase maternal and child morbidity and mortality. Methods: Data from three survey rounds of the Iracema-COVID cohort study, collected 6, 12, and 18 months after birth, showed the patterns of postpartum attendance to primary health care consultation of the mother-child dyad. Crude and adjusted multinomial logistic regressions with robust variance were used to assess factors associated with nonattendance. Results: Among the 314 cohort mothers, 25% did not attend any primary health care consultation during the 18-months postpartum, while 30% of the mothers did all three. Regarding the child, 75% had regular primary health care consultations in all three survey rounds, while 4% did not attend any in their first 18 months of life. By the end of the first COVID-19 wave, the proportion of mother and child who attended the consultations had fallen by 23 and 18%, respectively. The main factors associated with nonattendance were mothers aged below 25 years, and mothers with more than one child. Conclusion: An important delay or nonattendance to primary health care consultation by the mother-child dyad was observed during the COVID-19 pandemic. Such practice, with a high potential to increase maternal and child morbidity and mortality, was particularly frequent among younger mothers and those with more than one child.